Brand Love as a Mediator Between Emotional Stimuli and Loyalty Among Young Consumers in Machala, Ecuador (Journal SCIENCEVOLUTION, 2025)
This study examines the role of Brand Passion and Brand Sensuality as brand attributes in the construction of Brand Love, and how this influences emotional connections and Brand Loyalty in entertainment and leisure centers in the city of Machala, Ecuador. The research employs a quantitative approach, applying a PLS-SEM model to analyze the relationship between the aforementioned variables. A survey was conducted with 330 young individuals, aged 18 to 30, who regularly attend these establishments. The results reveal that Brand Sensuality and Brand Passion significantly influence the development of Brand Love, with sensuality being the variable with the greatest impact on both Brand Love and Brand Loyalty. In contrast, Brand Passion did not show a significant direct relationship with Brand Loyalty, suggesting the need to provide multisensory experiences and updated strategies to consolidate loyalty. This study contributes relevant knowledge to the experiential marketing sector, highlighting the importance of sensory and emotional stimuli in creating lasting bonds with consumers through Brand Passion and Brand Love.
Keywords: Brand Love; Brand Loyalty; Brand Sensuality; Brand Passion; Machala